Analisis Kesuksesan Sistem Informasi dengan Pendekatan Model Kesuksesan Sistem Informasi DeLone & McLean - Ajeng Wahyu Tri Yulinda; Azka Ubaidillah; Yunarso Anang (Politeknik Statistika STIS, 2022)
SIPADU-STIS is an information system used at the Politeknik Statistika STIS to support the implementation of academic activities on campus. SIPADU-STIS was developed in 2010 and has been used as the main information system at Politeknik Statistika STIS up to now. However, there is no specific research has been conducted on the factors that influence the success of the SIPADU-STIS. The information system that has been implemented needs to be studied for its success and the factors that influence it. The criteria in this study refers to the DeLone & McLean Information System Success Model that has been modified. The aim is to determine the variables that influence the success of SIPADU. The focus of this research is SIPADU-STIS Web Portal for Students. The variables studied include system quality, information quality, service quality, user satisfaction, and net benefits. The result is that all predictor variables have a significant positive effect and provide validation to the model. There are some recommendations based on the analysis that would be a concern for the on-going SIPADU development.